Conceptualizing Public Service Equity and Equality in Kenya: Towards Zero Unemployment - Amukowa, Wycliffe (International J. Soc. Sci. & Education, 2013)
The issue of unemployment, defined in this paper as lack of jobs, lingers many minds in Kenya. It is alleged that unemployment is the root cause of poverty, crimes, illiteracy, poor health care among others unfavourable conditions that continue to afflict the people of Kenya today. It is in this state of afflictions that prescriptive philosophers seek to challenge the human mind as far as possible in trying to understand basic issues such as suffering, pain, death, happiness, good and evil, which they seek to explain by speculation. This paper is a speculative engagement of Public Service Equity and Equality practice as a panacea to the alleviation of the problem of unemployment and its resultant afflictions in Kenya.
Keywords: Equity; Equality; Development; Unemployment; Practice